Aplicación de minicomputadoras - Portilla Roberton, Marcial; Ruiz Ascencio, José; Guzmán Arenas, Adolfo (My University, 1975)
The number of areas in our modern society where digital computers are now employed is truly remarkable. Computers are used in our banks; airlines and train companies use them to make reservations, in schools the bookkeeping and sometimes even class scheduling are done by computer. They are used in the control systems for large factories and to navigate and guide everything from space vehicles to submarines computers help design and then control the operation of nuclear reactors help manage hospitals and monitor patients recovery, record our births and deaths on government records.
Keywords: sistemas numéricos; fallas eléctricas; teletipos; cintas magnéticas; tarjetas perforadas